Common antigenic structures of HL-A antigens. VI. Common antigenic determinants located on the 33,000 Dalton alloantigenic fragment portion of papain-solubilized HL-A molecules. - Nakamuro, K (1975)
HL-A 33,000 Dalton fragments were isolated from three papain-solubilized HL-A preparations carrying different HL-A allospecificity by the dissociation induced in the reaction with rabbit antibodies to HL-A 11,000-Dalton fragment (i.e. human beta2-microglobulin). By assaying the binding activity with rabbit antisera against papain-solubilized HL-A molecules and against each of the HL-A component fragments and also with a battery of HL-A alloantisera, the 'antibody-dissociated' 33,000-Dalton fragments were shown to retain not only the HL-A alloantigenic determinants but also the HL-A common antigenic determinants that are native to the 33,000-Dalton fragment portion of undissociated HL-A molecules and to be devoid of the cryptic HL-A common antigenic determinants that are found on HL-A 33,000-Dalton fragments obtained by dissociation with chemical reagents including acid. However, on exposure to acid, the antibody-dissociated 33,000-Dalton fragments were found to lose their HL-A alloantigenic and common antigenic characteristics and gain the cryptic HL-A common antigenic determinants. The greater part of the HL-A common antigenic determinants found here appears to be primate cross-reacting determinants.